LEARNING ECOSYSTEM IN THE CONTEXT OF THE CONCEPT OF DIGITAL TRANSFORMATION OF EDUCATION AND SCIENCE OF UKRAINE - Tarasenko, Nataliya (Collection of scientific papers «ΛΌГOΣ», 2022)
The global crisis in many areas of human life caused by the COVID-19 pandemic has accelerated the digitalization of many processes. Many people tried to continue their activities online, such as work, study, trade, etc [1].